2003
DOI: 10.1002/ppul.10342
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of patients with cystic fibrosis on preventive counseling and transition to adult care

Abstract: The purpose of this study was to investigate how adolescents and adults with cystic fibrosis (CF) view preventive counseling and their transition to adult-centered care within a children's hospital. Thirty-two patients >/=16 years old diagnosed with CF were recruited from a pediatric tertiary care setting. During face-to-face interviews, patients were asked 27 structured questions and completed a 30-item self-administered questionnaire on preventive counseling by healthcare providers and on transition issues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 35 publications
1
61
1
Order By: Relevance
“…Across several studies, patients described CCC as a familiar and comfortable environment, and reported attachment and feelings of trust toward their health care providers [21][22][23][24][25][26][27][28][29][30][31][32]. Recent findings suggest that the main barrier patients faced after transition was to "detach themselves" from the pediatric team [33].…”
Section: Patients' Feelings and Concernsmentioning
confidence: 99%
“…Across several studies, patients described CCC as a familiar and comfortable environment, and reported attachment and feelings of trust toward their health care providers [21][22][23][24][25][26][27][28][29][30][31][32]. Recent findings suggest that the main barrier patients faced after transition was to "detach themselves" from the pediatric team [33].…”
Section: Patients' Feelings and Concernsmentioning
confidence: 99%
“…Care for young adults with CF is an example of a situation in which adult and pediatric providers work together to successfully transfer care provided in children's hospitals to adult care settings. 4,23,29 Young adults with CHD, on the other hand, have high health care utilization, which increases with age. 38 However, CHD is much more heterogeneous, and encompasses Ͼ100 separate conditions that require specialized medical, surgical, and imaging equipment and personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the best location for the care of adults with chronic conditions that originate in childhood is a topic that is addressed in a growing body of literature 4,[16][17][18]23,29,37 but remains unclear. A key question is the role of children's hospitals and whether they provide care for children only or for all patients with childhood diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations